A novel model to simulate cloud dynamics with cellular automaton. (December 2019) - Silva, Alisson R.; Silva, Adma R.; Gouvêa, Maury M.
Abstract: In real system simulations, the application of cellular automata has been shown as an interesting option, because it can represent an emergent behavior and its implementation is simple. This paper presents a method for simulating thermodynamic systems, such as cloud dynamics, with cellular automata. In accordance with thermodynamic principles, this paper presents an isolated system model that describes temperature dynamics. The model uses the Von Neumann neighborhood of five cells, each with two possible states: the presence or absence of a cloud or a part of it. Our model uses three weather properties, as follows, condensed cloud water particles, temperature and outer winds. Four types of experiments were performed to validate the model proposed: (i) a warm body in the environment, (ii) a cloud dynamic simulation, (iii) a stability analysis, and (iv) a comparison between the dynamic of the proposed model and satellite images of clouds. Highlights: This paper presents a method for simulating thermodynamic systems, such as cloud dynamics, with cellular automata. The model proposed uses the Von Neumann neighborhood of five cells. Our model uses three weather properties: condensed cloud water particles, temperature, and outer winds. Three of experiments are performed: a warm body, other to analyze the system stability, and a cloud dynamics analysis.